Maximal and explosive strength of high-level alpine skiers after severe lower extremity injury: a retrospective comparison with non-injured skiers - Trachsel, S.; Gross, M.; Bruhin, B.; Baur, H.; Hübner, K. (Sports, 2025)
Before returning to sport (RTS) following lower extremity injury, competitive alpine skiers` performance strength profiles should be verified. This study examined whether differences in maximal isometric (Fmax) and explosive strength (Pmax) exist between non-injured (n_INJ) and post-injured (p_INJ) elite skiers (n = 56) after RTS. It also explored whether Fmax and Pmax values recover differently over time and whether restoration rates differ between males and females. An explorative analysis was conducted to determine differences in back-squat Fmax and Pmax during squat (SJ) and countermovement jumps (CMJ) without and with additional load. Data were available from before injury and after athletes` RTS for p_INJ or twice across a comparable time span for n_INJ. While differences between n_INJ and p_INJ after rehabilitation are not significant for Fmax, p_INJ generally display significantly lower Pmax (r = 0.34-0.40). Additionally, results suggest that Fmax is restored first, followed by Pmax without eccentric component (SJ), and that Pmax (CMJ) with eccentric component is restored slowest. Further, p_INJ showed lower Pmax in loaded jumps even before injury (p = 0.035-0.047, r = 0.36-0.39). Finally, females display generally lower Pmax for a given Fmax. Overall, these results contribute to improving rehabilitation and prevention.